ChemInform Abstract: InCl3‐Catalyzed Synthesis of 1, 2‐Dimetallic Compounds by Direct Insertion of Aluminum or Zinc Powder. Issue 9 (5th March 2013) - Bluemke, Tobias D.; Klatt, Thomas; Koszinowski, Konrad; Knochel, Paul
Abstract Conversion of aromatic 1, 2‐dibromides or analogous 1‐bromo‐2‐triflates into 1, 2‐dimetallic species, which can be isolated, is dramatically improved by catalytic amounts of InCl3.